Wilson’s Disease in an Elderly Patient - Maziar Badii; Henry Wong; Urs P Steinbrecher; Hugh J Freeman (Canadian Journal of Gastroenterology)
A 65-year-old man with Fanconi’s syndrome was investigated for the cause of chronic liver disease. Wilson’s disease was diagnosed based on the detection of bilateral Kayser-Fleischer rings, a low serum ceruloplasmin level, increased urine copper excretion and positive histochemical stains of his liver for copper. This case is unusual because of the patient’s elderly age at the time of diagnosis and the absence of neurological changes due to Wilson’s disease in spite of advanced hepatic disease and the presence of Kayser-Fleischer rings. Even in the elderly patient, Wilson’s disease should be considered a possible cause of chronic liver disease.